Preparation of Chitosan Nanoparticles Loaded by Dexamethasone Sodium Phosphate: Chitosan nanoparticles loaded by dexamethasone - Amir Dustgania,; Ebrahim Vasheghani Farahani,; Mohammad Imani, (Iranian Journal of Pharmaceutical Sciences, 2008)
Biodegradable nanoparticulate carriers, have important potential applications for administration of therapeutic molecules. Chitosan based nanoparticles have attracted a lot of attention upon their biological properties such as biodegradability, biocom-patibility and bioadhesivity. The aim of the present investigation was to describe the synthesis and characterization of novel biodegradable nanoparticles based on chitosan for encapsulation of dexamethasone sodium phosphate. To achieve this objective, ionic gelation method were used. Drug containing nanoparticles were prepared with different amounts of drug. The mean size and size distribution of nanoparticles were measured by dynamic laser light scattering. The mean particle size, varied in the range of 250-350 nm. Values of loading capacity and loading efficiency varied between 33.7%-72.2% and 44.5%-76.0% for prepared nanoparticles.